PEMIKIRAN AHMAD TAFSIR TENTANG GURU DALAM PENDIDIKAN ISLAMI DAN RELEVANSINYA DENGAN SISTEM PENDIDIKAN NASIONAL - Badruzaman, Jajang (Tawazun: Jurnal Pendidikan Islam, 2019)
Teachers in Islam are the ones who are responsible for the development of the students by seeking all their potential, both affective potential, cognitive potential, and psychomotor potential. Teachers also mean responsible adults to provide help to the students in their physical and spiritual development in order to reach maturity level, and be able to stand alone in fulfilling their duties as servants of God. The focus of the problem in this study is to examine Ahmad Tafsi's thinking about teachers in Islamic education and its relevance to the National Education System Law. The purpose of this research is to increase the knowledge of whether Ahmad Tafsir's thoughts on Teachers in Islamic education are relevant to the National Education System Law. The method used is descriptive qualitative by using approach of research of library research or library research. The research technique used is analysis study. From the results of this study the researchers found that Ahmad Tafsir's thought about teachers in Islamic education is the task of teachers is to educate, the task of most teachers is to educate by way of teaching. Being a qualified teacher is certainly not just teaching but must meet the nature and requirements that reflect the teacher is professional, authoritative, appropriate to be obeyed and followed, responsible, and others. Keywords : Teachers, Islamic education; Sisdiknas No 14 of 2005 on Teachers and Lecturers, Relevance of thought